2015
DOI: 10.1037/xhp0000097
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic neural field model of temporal order judgments.

Abstract: Temporal ordering of events is biased, or influenced, by perceptual organization—figure–ground organization—and by spatial attention. For example, within a region assigned figural status or at an attended location, onset events are processed earlier (Lester, Hecht, & Vecera, 2009; Shore, Spence, & Klein, 2001), and offset events are processed for longer durations (Hecht & Vecera, 2011; Rolke, Ulrich, & Bausenhart, 2006). Here, we present an extension of a dynamic field model of change detection (Johnson, Spenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Target detection was enhanced when the target fell within the region observers currently perceived as the ‘figure’ suggesting a perceptual advantage for targets appearing in figure relative to background regions. Similarly, Nelson and Palmer (2007) showed that when observers viewed a figure-ground display in which one region contained a meaningful, or familiar, cue to figure-ground assignment (e.g., a face in profile), targets falling within this region were detected more quickly, likely because perceptual processing of these ‘figures’ began prior to perceptual processing of grounds (Lester, Hecht, & Vecera, 2009; see also Hecht, Spencer, & Vecera, 2015). In addition to this effect of figural status on detection times, Nelson and Palmer also found better discrimination for targets appearing in figures.…”
Section: Consequences Of Figure-ground Assignmentmentioning
confidence: 97%
“…Target detection was enhanced when the target fell within the region observers currently perceived as the ‘figure’ suggesting a perceptual advantage for targets appearing in figure relative to background regions. Similarly, Nelson and Palmer (2007) showed that when observers viewed a figure-ground display in which one region contained a meaningful, or familiar, cue to figure-ground assignment (e.g., a face in profile), targets falling within this region were detected more quickly, likely because perceptual processing of these ‘figures’ began prior to perceptual processing of grounds (Lester, Hecht, & Vecera, 2009; see also Hecht, Spencer, & Vecera, 2015). In addition to this effect of figural status on detection times, Nelson and Palmer also found better discrimination for targets appearing in figures.…”
Section: Consequences Of Figure-ground Assignmentmentioning
confidence: 97%